EEG Functional Connectivity and Cognitive Variables in Premanifest and Manifest Huntington’s Disease: EEG Low-Resolution Brain Electromagnetic Tomography (LORETA) Study - Delussi, Marianna; Nazzaro, Virgilio; Ricci, Katia; de Tommaso, Marina (Frontiers in Physiology, 2020)
BACKGROUND: Scientific literature does not offer sufficient data on EEG functional connectivity and its correlations with clinical and cognitive features in premanifest and manifest HD. AIM: This study tries to identify abnormal EEG patterns of functional connectivity, in conditions of "brain resting state" and correlations with motor decline and cognitive variable in Huntington's disease, in premanifest and manifest phase, looking for a reliable marker measuring disease progression. METHOD: Observational cross-sectional study; 105 subjects with age ≥ 18 years submitted to HD genetic test. Each subject underwent a neurological, psychiatric and cognitive assessment, EEG recording and genetic investigation (CAG trait). EEG connectivity analysis was performed by means of exact Low Resolution Electric Tomography (eLORETA) in 18 premanifest HD, 49 manifest HD and 38 control subjects. RESULTS:HD patients showed a Power Spectral Density reduced in the alpha range and increased in delta band compared to controls; no difference was detectable between premanifest HD and manifest HD; the Global Connectivity in premanifest HD revealed no significant differences if compared to manifest-HD. The Current Source Density was similar among groups. No statistically significant results when comparing premanifest HD with contol group, even in comparison of manifest-HD with Controls, and premanifest HD with manifest HD. Manifest HD compared to Controls showed a significant increase in delta, alpha1, alpha2, beta2 and beta3. Lagged Phase Synchronization in delta, alpha1, alpha2, beta2 and beta3 bands was increased in HD compared to controls (t= -3.921, p<0.05). A significant correlation was found in Regression Analysis: statistically significant results in premanifest HD for the Simbol Digit Modality Test and lagged phase synchronization” in the Beta1 (r= -0.806, p<0.05) in the prefrontal regions. The same correlation was found in manifest-HD for the Stroop Word Reading Test in the Alpha2 band (r= -0.759, p<0.05). CONCLUSION: Increased phase synchronization in main bands characterized EEG in HD patients, as compared to controls. Premanifest HD were not dissimilar from manifest HD as regard to this EEG pattern. Increased phase synchronization correlated to cognitive decline in HD patients, with a similar trend in premanifest HD, suggesting that it would be a potential biomarker of early phenotypical expression.